1958
DOI: 10.2134/agronj1958.00021962005000030004x
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Genotypic and Environmental Variances and Covariances in Upland Cotton and Their Implications in Selection1

Abstract: Synopsis Plot error variances were large for lint yield, bolls per plant, seed per boll, and boll weight; small for lint percentage, seed and tint index, and fiber length, strength and fineness. Genotype x environment interaction variances were generally small for all traits except yield and bolls per plant. Lint yield was highly positively correlated with lint percentage and bolls per plant and negatively correlated with seed index and weight per boll.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
300
1
5

Year Published

1977
1977
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 409 publications
(310 citation statements)
references
References 0 publications
4
300
1
5
Order By: Relevance
“…Day to maturity ranged from 94.00 to 126.67 days with average of 111.48 days. The estimate of PCV (10.20%), GCV (10.07%), and Panse and Shukhatme, 1969Jonson et al 1955Miller et al, 1958 Dewey and Lu 1959 .06 %), indicating the role of additive gene expression of these traits and have better scope for improvement of these traits through direct selection. Similar with our present finding, ( ) recorded high heritability along with moderate to high genetic advance in plant height, number of spikelets per panicle, days to maturity and days to 50% flowering while assessing the genetic parameters of rice.…”
Section: Resultsmentioning
confidence: 94%
“…Day to maturity ranged from 94.00 to 126.67 days with average of 111.48 days. The estimate of PCV (10.20%), GCV (10.07%), and Panse and Shukhatme, 1969Jonson et al 1955Miller et al, 1958 Dewey and Lu 1959 .06 %), indicating the role of additive gene expression of these traits and have better scope for improvement of these traits through direct selection. Similar with our present finding, ( ) recorded high heritability along with moderate to high genetic advance in plant height, number of spikelets per panicle, days to maturity and days to 50% flowering while assessing the genetic parameters of rice.…”
Section: Resultsmentioning
confidence: 94%
“…The heritability was estimated as per the formula suggested by Burton and De Van (1953) and the expected advance was calculated by the formula given by Johnson et al, (1955). The Genotypic and phenotypic correlation coefficients were worked out using the formulae suggested by Miller et al, (1958) and path analysis was carried out as suggested by Dewey and Lu (1959) so as to study the direct and indirect contribution of component characters on green yield of amaranthus species.…”
Section: Methodsmentioning
confidence: 99%
“…Correlation coefficients were calculated in all possible combinations taking all the characters into consideration at genotypic, phenotypic and environmental levels by using the formula as proposed by Miller et al, (1958).…”
Section: Correlation Coefficientsmentioning
confidence: 99%